EFEKTIVITAS MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN KOLABORASI PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Nur Alya R; Agus Muharam; Atep Lesmana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the effectiveness of the Project Based Learning (PjBL) model in improving the collaborative skills of fourth-grade students in Science and Social Studies (IPAS) learning. The study was motivated by students' low ability to work collaboratively, participate actively in group discussions, and share responsibilities equally. A quantitative approach was employed using the Pre-Experimental Design method with a One Group Pretest–Posttest Design. The sample consisted of 20 fourth-grade students from SDS Sartika, Karawang Regency, selected through a total sampling technique. Data were collected using a collaboration skills observation sheet. The Paired Sample T-Test revealed a significance value of 0.000 (p < 0.05), indicating a significant improvement in students' collaborative skills after the implementation of PjBL. The mean score increased from 53.50 to 84.25. The N-Gain score of 0.68 was classified as moderate, while Cohen's d value of 4.434 indicated a large effect size. Therefore, the Project Based Learning model was proven to be effective in enhancing students' collaborative skills in fourth-grade IPAS learning.